KORELASI MINAT BACA DENGAN KETERAMPILAN MENULIS KARYA ILMIAH MAHASISWA PGMI UIN ANTASARI BANJARMASIN - Khairunnisa Khairunnisa; Adha Khairina (PRIMARY EDUCATION JOURNAL (PEJ), 2020)
This study aims to find out how student’s reading interest is, how student’s writing skill of scientific is and whether there is a correlation between reading interest toward the scientific writing skills of students of PGMI UIN Antasari Banjarmasin class 2015 academic year 2017/2018. This type of research is field research with a quantitative approach. The sample of this research are 40 students of PGMI department taken by proportional sampling. Student’s reading interest data collected from questionnaire and student’s academic writing skill data is collected using some student’s scientific work collections which is assessed. The data were analyzed with statistical correlation with the product moment correlation. Based on the results of study, it is concluded that the students of PGMI UIN Antasari Banjarmasin class of 2015 academic year 2017/2018 had a reading interest at a good level with an average score of 70.92. The skill to write scientific works for PGMI students has a sufficient level with an average value (mean) of 76.62. There is a significant correlation between reading interest toward the writing skills of PGMI Student with a correlation coefficient of 0.385.